Kluth type IIIb9variant of esophageal atresia - Rahul Gupta; Ankit Singh; Arun Kumar Gupta (Wolters Kluwer Medknow Publications, 2020)
We, herein, present an extremely rare case of an esophageal atresia (EA) with distal tracheoesophageal fistula (TEF) with additional perforated membrane at the lower one-third of fistula. A neonate presented with difficulty in breathing and excessive frothing from the mouth. Radiograph with red rubber catheter in situ(obstruction at 10 cm from the gum margins) suggested EA with distal TEF. During thoracotomy, after ligation of fistula, a 6 Fr infant feeding tube was introduced into the distal esophagus which revealed obstruction at the lower one-third. An esophagotomy was performed; a membrane with opening at the center was identified. Following its excision, the esophageal end became dusky necessitating esophagostomy and feeding gastrostomy. A high index of suspicion for membranous obstruction at the lower one-third of fistula should be kept in mind while dealing with EA with distal TEF.